2005
DOI: 10.1093/humrep/deh708
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous or identity-registered sperm donors? A study of Dutch recipients' choices

Abstract: BACKGROUND: The aim of the present study was to gain insight into parents' own donor preferences within a system offering the choice between an anonymous and identity-registered donor. A comparison was made between recipients choosing for an anonymous donor (AD choosers) and those choosing for an identifiable donor (ID choosers) with regard to their sexual orientation, demographic characteristics, disclosure issues and infertility distress. METHODS: Data from 105 couples (61% heterosexual, 39% lesbian) were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 16 publications
(16 reference statements)
5
44
1
7
Order By: Relevance
“…The results from this study confirm those of other studies: where lesbian couples appear most inclined to disclose (Baetens and Brewaeys, 2001;Brewaeys et al, 2005;Freeman et al, 2009;Scheib et al, 2003) and that one of the documented reasons for not disclosing donor origins is the lack of information about the donor (Cook et al, 1995). As with the study of non-biological parents , where only nine non-biological parents expressed having no intention of ever disclosing to their child the nature of their conception, the current study found that only about 5.0% (83) of respondents had no intention of telling.…”
Section: Disclosuresupporting
confidence: 91%
See 1 more Smart Citation
“…The results from this study confirm those of other studies: where lesbian couples appear most inclined to disclose (Baetens and Brewaeys, 2001;Brewaeys et al, 2005;Freeman et al, 2009;Scheib et al, 2003) and that one of the documented reasons for not disclosing donor origins is the lack of information about the donor (Cook et al, 1995). As with the study of non-biological parents , where only nine non-biological parents expressed having no intention of ever disclosing to their child the nature of their conception, the current study found that only about 5.0% (83) of respondents had no intention of telling.…”
Section: Disclosuresupporting
confidence: 91%
“…There was a marked difference between cohorts in initial preference for using an open-identity donor -a similarly higher proportion of single respondents and those in a lesbian relationship deliberately chose an open-identity donor than did respondents in a heterosexual relationship. This confirms the findings of Brewaeys et al (2005) and Scheib et al (2003). A majority of respondents who had used an anonymous donor indicated that they wished they had used an open-identity donor, and a majority of all respondents endorsed the rights of donor-conceived offspring to discover their donor's identity.…”
Section: Choice Of Donorsupporting
confidence: 80%
“…This is in line with the Swedish legislation and what the fertility clinics are instructed Only the family 76 (18) 8 (7) 17 (17) 15 (14) 36 (34) <0.000 Friends/others (but not family) 31 (7) 6 (6) 8 (8) 7 (7) 10 (10) NS Family and friends/others 286 (68) 92 (84) 67 (66) 77 (73) 50 (48) <0.000 Not anyone 27 (6) 3 (3) 9 (9) 6 (6) 9 (9) NS a Chi-square test (35) 145 (34) 29 (27) 40 (37) 40 (37) 28 (28) 39 (39) 34 (34) 25 (23) 43 (40) 39 (36) 47 (44) 27 (26) 32 (30) 0.028 a Chi-square test to recommend their clients. The child"s right to know how she/he was conceived was stated clearly among the recipient couples, a view that confirms similar findings among gamete recipient couples who are in favour of disclosure (Brewaeys, de Bruyn, Louwe, & Helmerhorst, 2005) as well as among the general population in Sweden (Skoog Svanberg, et al, 2003).…”
Section: Discussionsupporting
confidence: 75%
“…Brewaeys and co-workers (Brewaeys, et al, 2005) Almost all of participants had told someone outside the couple about the donation treatment, which is an increase compared to earlier reports from Sweden (Gottlieb, et al, 2000;Lalos, et al, 2007). This may be interpreted as a change towards more openness concerning donation treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Notably, Brewaeys, de Bruyn, Louwe, and Helmerhorst (2005) found that all but one of the 41 lesbian couples surveyed in a recent Dutch study consciously chose identifiable rather than anonymous donors--a significantly higher proportion than among heterosexual couples--suggesting very little basis for claims of lesbian "maternal egoism". Additional implicit requirements, however, may operate in terms of the need for these women to monitor their behaviour and self-presentation to offer reassurance of their "normality" and suitability for motherhood.…”
Section: External and Internal Surveillance Techniquesmentioning
confidence: 99%